Pre-service teachers’ attitudes towards integrating technology in inclusive education - Miaomiao, Wu; DeWitt, Dorothy; Naz, Nor Nazrina Mohamad; Alias, Norlidah; Hong, Lee Leh (Intelektual Pustaka Media Utama, 2025)
Pre-service teachers’ attitudes influence their integration of technology into their inclusive practices, yet there is still a lack of research in academia assessing their level of attitudes. This study aimed to design an instrument to measure and investigate pre-service teachers’ attitudes toward integrating technology in inclusive education in Malaysia. One hundred and seventy-nine teacher trainees from a public university in Malaysia participated in this study. Two dimensions were identified through exploratory factor analysis, supported by a strong model fit in confirmatory factor analysis. Convergent validity was also satisfactory. Furthermore, all reliability coefficients exceeded 0.8. The outstanding reliability and validity of the instrument indicated its suitability for evaluating the attitudes of pre-service teachers. The results of the assessment showed that teachers’ attitudes were positive. Pre-service teacher training should be actively strengthened to promote the effective integration of technology in inclusive classroom.